The normalisation of relations between Kosovo and Serbia : how the EU can secure the implementation of the "European proposal" - Vulović, Marina (2023)
Zusammenfassung: Over the new year, tensions between Serbia and Kosovo rose once again. This occurred in the context of negotiations on a new European Union (EU) proposal - also known as the Franco-German or "European" proposal aimed at formalising relations between Belgrade and Pristina, much along the lines of the 1972 Basic Treaty between the two Germanys. On 27 February, there was a breakthrough in the negotiations: Both sides agreed on the text of the proposal, although it has not yet been signed. Additionally, the prioritisation of individual issues in the so-called implementation map has not yet been determined, which could cause further disputes. To ensure the adoption and full realisation of the agreement, the EU should not only assess its progress in the context of the EU accession negotiations of both countries. It should also establish specific implementation and monitoring mechanisms that will secure more modest interim targets for the implementation of individual issues in the agreement. This is the only way to successfully implement the new agreement